Problems Of Restriction On Civil Rights And Human Freedoms In The Legislation And Law Enforcement Practices Of Kazakh-Stan - Zhanuzakova, Leila; Altinbekkyzy, Alua; Jumabayeva, Karlygash; Zhailin, Gabiden; Usserova, Aigul (Opción, 2019)
The article is concerned with issues related to the restriction on civil rights and human freedoms in the Republic of Kazakhstan. After studying crucial international documents in the field of human rights, scientific works of Western, Russian and Kazakh scholars, the authors of the article determined the functional content of restrictions on the rights and freedoms of individuals, their close and inseparable connection with the mechanism of human rights protection and the limits of individual freedom in society. The authors have thoroughly analyzed the Constitution and the existing legislation of Kazakhstan, which establish restrictions on the exercise of rights and freedoms. Considering the negative law enforcement practice of courts and law enforcement agencies, the legislative norms securing grounds and procedures for the implementation of restrictions on rights and freedoms have been subjected to critical analysis. Based on the conducted research, the authors have developed recommendations for improving the mechanism of restricting human rights and freedoms and ensuring their effective protection.